Pengaruh ROA dan ROE Terhadap Harga Saham pada Perusahaan Perbankan yang Terdaftar di BEI Tahun 2020-2024 - Rizal Maulana; Muhammad Saddam Ihza Husain; Nopiyanti Rahmawati; Alfiana Alfiana (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
The importance of stock investment in supporting the country's economic growth lies in its role in driving the development of the capital market, which provides funding for companies, enabling them to grow and expand their businesses. The banking sector, as a financial institution, plays a crucial role in maintaining national economic stability by contributing to the increase in capital formation, which is essential for economic development. Therefore, the capital market and the banking sector are closely interconnected in maintaining economic stability. One of the key elements of fundamental analysis is profitability ratios, including ROA and ROE. The aim of this study is to determine the extent of the correlation between ROA and ROE with stock prices. This research is a quantitative study using secondary data derived from the financial statements of banking companies from 2021 to 2025. The findings show that ROA and ROE have a positive influence on stock prices, both partially and simultaneously. This indicates that the banking sector demonstrates strong company performance, as the management of assets and equity—reflected in ROA and ROE—has been carried out optimally, thereby positively affecting stock prices.